2020
DOI: 10.1371/journal.pone.0244562
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal determinants of low birth weight among Indian children: Evidence from the National Family Health Survey-4, 2015-16

Abstract: Objective Low birth weight (LBW) is a serious public health problem in low- and middle-income countries and a leading cause of death in the first month of life. In India, about 18% of children are born with LBW (<2500 grams) in 2015–16. In this study, we aim to examine the influence of maternal factors and socio-demographic covariates on LBW in Indian children. Methods Data were drawn from the fourth round of the National Family Health Survey (NFHS-4), conducted in 2015–16. A cross-sectional study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 17 publications
8
36
0
Order By: Relevance
“…These practices determine what they eat, how much, why and when. Consequences of such beliefs are seen in health of women of childbearing age, in newborn babies and in infants and adolescents ( 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…These practices determine what they eat, how much, why and when. Consequences of such beliefs are seen in health of women of childbearing age, in newborn babies and in infants and adolescents ( 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies show that prevalence of LBW is almost near to our findings. [11][12][13] The reason could be; at tertiary health care settings the most of high-risk pregnancies are delivered. Another study from Tamil Nadu reported that the prevalence of LBW was 11.67%.…”
Section: Discussionmentioning
confidence: 99%
“…Severe problems with iron bioavailability related to a deficiency in micronutrients and severity of infectious and inflammatory diseases have been recently reviewed by Nair and Iyengar [ 16 ] and reported by others [ 72 ]. Chronic iron deficiency also has maternal determinants [ 73 ]. The amount of iron stored mainly depends on the gestational length period and birth weight of the baby.…”
Section: Disparities In India: Relevance Of Ida Risk Factorsmentioning
confidence: 99%